THE EFFECTIVENESS OF JĀTAKA PUPPET LEARNING MEDIA ON THE LEARNING INTEREST OF BUDDHIST DHAMMA METTA KALISAT SUNDAY SCHOOL STUDENTS. - Wibowo, Tabah Wisnu; Widiyono, Widiyono; Dewi, Sukhitta (Jurnal Pencerahan, 2023)
This study aims to determine the effectiveness of the jātaka puppet learning media on the learning interest of Buddhist Dhamma Metta Kalisat Sunday school students. The type of research used is a type of research that uses a classroom action research design. Data collection in this study using observation, documentation, and interviews, guided by observation sheets and interviews. The subjects of this classroom action research are Dhamma Metta Kalisat Buddhist Sunday School students at the Kindergarten, Elementary, and Junior High School levels. The results of this study indicate that students' interest in learning during the use of jātaka puppet learning media has increased. It can be proven by the results that were carried out before the use of the jātaka puppet, that the student's interest was 16 points or 40%. After using the media, students' interest in learning in the pre-cycle was 24 points with a percentage of 60%, in cycle 1 they got 26 or in percentage form it was 65%, and in the second cycle it reached 35 points and a total percentage of 87.5%. Therefore, it can be concluded that the use of wayang jātaka learning media is effective in increasing students' interest in learning at the Buddhist Dhamma Metta Kalisat Sunday School.